2012
DOI: 10.1371/journal.pone.0047532
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an Ordered, Comprehensive STM Mutant Library in Infectious Borrelia burgdorferi: Insights into the Genes Required for Mouse Infectivity

Abstract: The identification of genes important in the pathogenesis of Lyme disease Borrelia has been hampered by exceedingly low transformation rates in low-passage, infectious organisms. Using the infectious, moderately transformable B. burgdorferi derivative 5A18NP1 and signature-tagged versions of the Himar1 transposon vector pGKT, we have constructed a defined transposon library for the efficient genome-wide investigation of genes required for wild-type pathogenesis, in vitro growth, physiology, morphology, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
239
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(251 citation statements)
references
References 84 publications
(127 reference statements)
10
239
2
Order By: Relevance
“…1). Previous studies in our laboratory generated transposon mutants with mutations in these carbohydrate transporters (26). Individual PEP-PTS and cyaB STM mutant clones were examined by PCR using primers flanking the insertion sites to confirm the transposon insertion and thus ascertain that each clone represented a pure culture.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1). Previous studies in our laboratory generated transposon mutants with mutations in these carbohydrate transporters (26). Individual PEP-PTS and cyaB STM mutant clones were examined by PCR using primers flanking the insertion sites to confirm the transposon insertion and thus ascertain that each clone represented a pure culture.…”
Section: Resultsmentioning
confidence: 99%
“…S1 in the supplemental material); subsequently these clones were separated as pure cultures by replating. PCR analyses showed that two of the mutant clones previously determined (26) to have transposon insertions in ptsH or chbB did not have inserts in these regions (see Fig. S1 in the supplemental material); these clones were hence excluded from further experimentation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations